Pathophysiology and clinical manifestations of immune complex vasculitides - Sunderkötter, Cord; Golle, Linda; Pillebout, Evangéline; Michl, Christiane (Frontiers in Medicine, 2023)
Immune complex (IC) vasculitides present inflammations of vessel walls associated with perivascular deposition of immunoglobulins, mostly IC. They encompass systemic and skin-limited variants of IgA vasculitis (IgAV), cryoglobulinemic vasculitis (CV), rheumatoid, lupus and hypocomplementaemic vasculitides, serum sickness, as well as cutaneous IgM/IgG-vasculitis or recurrent macular (hypergammglobulinaemic or exertion-induced) vasculitis. Serum sickness and CV fulfil criteria of type III immune reaction when large lattices of IC precipitate at vessel walls and activate polymorphonuclear neutrophils (PMN). IgAV differs at least with regard to causes of deposition of IC which result from altered, hypoglycosidated IgA1 molecules. The conditions for increased generation of immunoglobulines or formation of IC and their perivascular deposition in either skin or systemic organs are different and not fully explored. Another common denominator of IC-vasculitides is the subsequent activation of PMN near the vessel wall via Fcy- or Fcα-receptors. Acute episodes of IgAV appear to require that PMN become preactivated by IgA1 or IC already in the circulation, which results in increased adherence and vessel-destructive NETosis. This binding of IgA1 to PMN is associated with increased serum levels of hypogalactosidated IgA1. The characteristic clinical picture of IgAV is that of palpable or retiform purpura with clear predilection for lower legs, probably due to stasis-related reduction in blood velocity, while in other IC vasculitides additional factors influence altered predilections. Our knowledge of distinct forms and different pathophysiological pathways of IC vasculitides has not yet resulted in targeted efficacious therapies, but antibodies to complement components or for e.g. systemic IgAV intestinal budesonide to reduce generation of mucosal IgA appear to new options.